COVID-19 and OECD Labour Markets: What Impact on Gender Gaps? - Monika Queisser (Intereconomics, 2021)
Across the board statements on who suffers most are not helpful and may actually be a disservice to the fight for greater gender equality.
Keywords: 330; Epidemie; Coronavirus; Arbeitsmarkt; Geschlechterunterschiede; OECD-Staaten